Phobias, history of ; Fight or flight response ; Subjective units of distress scale - Penney, Alexander; Teatero, Missy (My University, 2015)
Phobias: The Psychology of Irrational Fear is the definitive volume on a broad range of topics related to fears and phobias. After an introduction to the subject of fear and phobias, the encyclopedia presents approximately 200 A-Z, cross-referenced entries that address phobias from a variety of angles--types of fears, root causes, physiological and psychological effects, classification, and treatments. The work presents accurate, authoritative, and up-to-date information based on scientific evidence. The majority of the numerous contributors are anxiety disorder researchers and clinicians who possess cutting-edge knowledge of their areas of expertise.
Keywords: anxiety disorders; phobias; encyclopedias